The Role of Teachers in Implementing Pancasila Values ​​to Form the Nationalistic Character of Early Childhood - Dewi Pusparini; Ummu Khulsum; Mediyana , Mediyana (ATTAQWA: Jurnal Pendidikan Islam dan Anak Usia Dini, 2025)
This study aims to describe the role of teachers in the application of values ​​to form the character of nationalism in early childhood in PAUD Al Hikmah Tlanakan. The values ​​of Pancasila that are instilled include the values ​​of divinity, humanity, unity, democracy and social justice. This study uses a qualitative approach with a descriptive method. The subjects of the study were teachers and students. Data collection techniques were carried out through observation, interviews, and documentation. The results of the study showed that teachers have a strategic role in instilling Pancasila values ​​through learning activities, role models, habits, and daily social interactions. Children showed enthusiasm in participating in activities such as reading Pancasila, recognizing the state symbol, and mentioning the name of the president. For this reason, a more contextual and enjoyable method is needed so that these values ​​can be more easily understood and instilled from an early age.